2023
DOI: 10.3390/jox13040037
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Exudates as Biostimulants: Role in Plant Growth Promotion and Stress Mitigation

Mariya Ansari,
B. Megala Devi,
Ankita Sarkar
et al.

Abstract: Microbes hold immense potential, based on the fact that they are widely acknowledged for their role in mitigating the detrimental impacts of chemical fertilizers and pesticides, which were extensively employed during the Green Revolution era. The consequence of this extensive use has been the degradation of agricultural land, soil health and fertility deterioration, and a decline in crop quality. Despite the existence of environmentally friendly and sustainable alternatives, microbial bioinoculants encounter n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 241 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the application of microbial filtrates not only boosts nutrient uptake but also activates soil and plant-associated beneficial microbiota [ 90 ]. This dual action enhances plant resilience against pathogens and abiotic stresses, promoting a more sustainable agricultural practice by reducing the reliance on chemical fertilizers and pesticides [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the application of microbial filtrates not only boosts nutrient uptake but also activates soil and plant-associated beneficial microbiota [ 90 ]. This dual action enhances plant resilience against pathogens and abiotic stresses, promoting a more sustainable agricultural practice by reducing the reliance on chemical fertilizers and pesticides [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGPRs, PGPFs Microbial exudates Contribute to plant growth, plant defense, and biotic and abiotic stress control (Ansari et al, 2023)…”
Section: Roles Referencesmentioning
confidence: 99%